ANALISIS MISKONSEPSI PESERTA DIDIK PADA MATERI KINEMATIKA GERAK LURUS DENGAN MENGGUNAKAN TES DIAGNOSTIK DI KELAS X MA NEGERI PEKANBARU - Ulfa Indra Yuni; Fakhruddin Z Fakhruddin Z; Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to determine the level of students misconception on linear kinematics motion material by the application of diagnostic test at X class of MAN 1 Pekanbaru and MAN 2 Pekanbaru. The total population was 165 students which all of X class students of MAN 1 Pekanbaru and MAN 2 Pekanbaru. The research instrument used is diagnostic test. The data was obtained by giving diagnostic test to students were after linear kinematics motion had been learnt. The data was analayse by using descriptive analysis and percentage teqnique which gave the description about students misconception level. The result showed that the percentage of average students at X class of MA Negeri Pekanbaru misconception was 59.76% with moderate level of misconception.Keywords: Misconception, diagnostic test, linear kinematics motion.